Classroom Action Research Training Teacher Physical Education, Sports and Health in Padang City - Masrun Masrun Masrun (Jurnal Berkarya Pengabdian Masyarakat, 2019)
In Teaching-learning process on class, teacher playing vital role for reaching planned education purpose. But that not an easy case, because there are many problems occur in class. Those problems have to be eliminated, and the way to do that is by using class room research. Class room action research is designed to solved a teaching-learning process on class. Class room action research purposed repairing learning process simultaniusly. Class room action research conducted simultaniously to repairing teaching-learning process naturally without disturbing teaching learning process it self. Class room action research conducted based on cycle. Each cycle play vital role fo the next cycle. By conducting training activity for education sports teachers for making and designing a classroom research, they will solve the problems occur in teaching-learning process. By developing education sports teacher ability in class room research will lead the educational purposed to optimal result. Training designed by using classical models, including: discussing, interview, guiding, and assinment. At the end of the training process, every education sports teaching producing one class room action research proposal and making one research based on their own class problem.